Pemberdayaan Keluarga Dhuafa Berbasis Filantropi Islam: Studi Kasus pada Keluarga Ibu Rohasih di Jakarta Selatan - Tasya Naura Rahma Dhani; Latifa Rahmawati; Erlisa Ramadani Raharja; Rifma Ghulam Dzaljad (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
The phenomenon of poverty remains a significant social issue in Indonesia, particularly in densely populated urban areas such as South Jakarta. This article discusses the empowerment of underprivileged families (dhuafa) through an Islamic philanthropic approach based on the theology of Al-Ma’un as taught by KH. Ahmad Dahlan, the founder of Muhammadiyah. A case study was conducted on the family of Mrs. Rohasih, who experiences limitations in economic resources, education, and access to basic facilities. The empowerment program implemented includes the provision of business capital, food assistance, and school supplies. The outcome of this initiative is expected to improve the family's standard of living independently, reduce dependency, and foster students’ social awareness in practicing humanitarian values. This article emphasizes the importance of synergy between educational institutions, the community, and religious values in addressing structural poverty.